Pattern recognition receptors and their roles in antiviral innate immunity in livestock - Liu, Shujing; Qi, Junpeng; Wang, Yuxin; Liu, Minglu; Su, Monong; Wang, Liang; Li, Minghua; Zhao, Zimo; Chen, Jilin (Frontiers in Immunology, 2026)
Viral infectious diseases pose a persistent challenge to global livestock production, animal welfare, and food security, emphasizing the critical role of early host defense mechanisms in limiting viral replication and transmission. As frontline sensors of infection, pattern recognition receptors (PRRs) detect viral nucleic acids and trigger antiviral innate immune responses via coordinated downstream signaling. This review summarizes the functions of three major PRR families, Toll-like receptors (TLRs), RIG-I-like receptors (RLRs), and the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway, emphasizing their involvement in detecting viral agents and activating downstream pathways, including NF-κB and IRF3/7. Particular attention is given to how these receptors function in pigs and poultry, highlighting their immune responses to economically significant viruses such as porcine reproductive and respiratory syndrome virus (PRRSV), African swine fever virus (ASFV), avian influenza virus (AIV), and Newcastle disease virus (NDV). The mechanisms by which PRRs activate interferon-mediated immune responses, as well as viral strategies to evade detection, are systematically discussed. Additionally, the review explores recent advances in understanding PRR signaling specificity across species, and their potential applications in vaccine adjuvant design or antiviral drug development are also reviewed. By integrating these insights, this work provides a theoretical foundation for improving disease prevention and control in livestock production.